2020
DOI: 10.1007/s00784-020-03646-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioadhesion in the oral cavity and approaches for biofilm management by surface modifications

Abstract: Background All soft and solid surface structures in the oral cavity are covered by the acquired pellicle followed by bacterial colonization. This applies for natural structures as well as for restorative or prosthetic materials; the adherent bacterial biofilm is associated among others with the development of caries, periodontal diseases, peri-implantitis, or denture-associated stomatitis. Accordingly, there is a considerable demand for novel materials and coatings that limit and modulate bacterial attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 304 publications
(384 reference statements)
3
123
0
5
Order By: Relevance
“…[1,2]. The acquired oral pellicle covers tissues and dental materials in the oral cavity [2]. It functions, e.g., as a protective layer and contains In vitro studies showed the antifungal (Candida spp.)…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1,2]. The acquired oral pellicle covers tissues and dental materials in the oral cavity [2]. It functions, e.g., as a protective layer and contains In vitro studies showed the antifungal (Candida spp.)…”
Section: Introductionmentioning
confidence: 99%
“…In general, adhesion of proteins and microorganisms, e.g., Candida to biomaterials depends on several factors such as surface charge, surface free energy, polarity, hydrophobicity, morphology, and roughness, as well as the composition of biomaterials. [ 1 , 2 ]. The acquired oral pellicle covers tissues and dental materials in the oral cavity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deposition of plaque biofilms on the surfaces of dentures has been a troublesome factor that directly affects the local and systemic health of the patients [83]. Management strategies to prevent plaque biofilm formation on the acrylic surface of removable appliances have been attempted using two primary methods: (1) adding microbial-resistant filler components at the micro and nanoscale [23] and (2) improving the surface properties of the fabricated appliances by coatings [84,85]. The ZPs show the possibility of action via both of the above interventions, and multiple studies in recent years have detailed promising findings in this direction of work.…”
Section: Removable Appliancesmentioning
confidence: 99%